6 - Education, caractères et développement: by Denis Amoussou-Yeye - Denis Amoussou-Yeye (Africa Development, 1996)
Francophone African educational systems are in crisis. The causes are to be found in the legacy of the colonial educational system which inculcated exogenous ideological constructions and contributed to fostering attitudes and behaviours inimical to the development of individual personalities. As development should be centred on human beings, Africa needs educational systems geared towards the development and realization of individual potentialities and aspirations, through educational programmes which combine knowledge, savoir-faire and savoir-être.